Isolation and characterization of two peptides with prolactin release-inhibiting activity from porcine hypothalami. - Schally, A V (1991)
Two peptides with in vitro prolactin release-inhibiting activity were purified from stalk median eminence (SME) fragments of 20,000 pig hypothalami. Monolayer cultures of rat anterior pituitary cells were incubated with aliquots of chromatographic fractions and the inhibition of release of prolactin in vitro was measured by RIA in order to monitor the purification. The hypothalamic tissue extract was separated into 11 fractions by high-performance aqueous size-exclusion chromatography with one fraction showing a 4-fold increase in prolactin release-inhibiting factor (PIF) activity. This material was further purified by semipreparative reversed-phase (RP) HPLC. This process resulted in the separation of two distinct fractions that showed high PIF activity. These were further purified by semipreparative and analytical RP-HPLC to apparent homogeneity as judged by the UV absorbance profiles. Neither of the two peptides showed cross-reactivity with gonadotropin releasing hormone-associated peptide or with somatostatin-14 antibodies. Protein sequence analysis revealed that one of the PIF peptides was Trp-Cys-Leu-Glu-Ser-Ser-Gln-Cys-Gln-Asp-Leu-Ser-Thr-Glu-Ser-Asn-Leu-Leu- Ala-Cys - Ile-Arg-Ala-Cys-Lys-Pro, identical to residues 27-52 of the N-terminal region of the proopiomelanocortin (POMC) precursor (corresponding to amino acids 1-26 of the 16-kDa fragment). The sequence of the other PIF was Ala-Ser-Asp-Arg-Ser-Asn-Ala-Thr-Leu-Leu-Asp-Gly-Pro-Ser-Gly-Ala-Leu-Leu- Leu-Arg - Leu-Val-Gln-Leu-Ala-Gly-Ala-Pro-Glu-Pro-Ala-Glu-Pro-Ala-Gln-Pro-Gly-Val- Tyr, representing residues 109-147 of the vasopressin-neurophysin precursor. Synthetic peptides corresponding to the N-terminal region of POMC had significant PIF activity in vitro.